Satisfaction with life, psychological distress, and workplace bullying among construction workers - Muhammad Yuzar Virza; Dadan Erwandi; Fatma Lestari; Abdul Kadir (International Journal of Public Health Science (IJPHS), 2021)
Construction workers are among workers who have to face a very dynamic work situation with a fixed deadline because they have to finish the work according to the target of completion as stated in the contract. The study aimed to compare Satisfaction with Life, Psychological Distress, and Workplace Bullying of the workers in two construction companies. This is a cross-sectional study using a questionnaire distributed to two groups of workers who work in two different companies with a total number of respondents of 588. Data collected were then processed using a frequency distribution table and compared using the Mann Whitney method to identify differences between the two groups. The study showed differences between the workers from the two companies in terms of negative behaviors, level of distress, and level of satisfaction with life. Workers in the Civil Engineering Contractor Company suffer more bullying and a slightly higher level of distress. The lowest level of satisfaction with life is also seen in this company when compared to that of the engineering procurement construction (EPC) contractor company. The result of study indicate that difference might link to more bullying actions and a higher level of distress in the construction civil engineering company, which trigger dissatisfaction with life among its workers. Thus, management should act promptly to eliminate negative behaviors as it will be crucial in preventing the increase in the number of bullying victims and the level of distress in the workplace will not increase.